Efektivitas Elektrokoagulasi sebagai Metode Alternatif dalam Penurunan TDS dan Kesadahan pada Air Payau di Pulau Pasaran: Indonesia - Afriany, Chelsy; Fajar, Mutiara; Yanda, Rahma (Jurnal Sains & Teknologi Lingkungan, 2026)
This study aims to evaluate the efficiency of the electrocoagulation method in reducing TDS and hardness levels, as well as to analyze the effects of inter-electrode distance (1; 1.5; and 2 cm), applied voltage (15; 20; and 25 V), and contact time (20; 40; 60; and 80 minutes). The initial concentrations of brackish water samples were measured prior to treatment, and the samples were subsequently processed using an electrocoagulation reactor. The highest TDS removal efficiency was achieved at an inter-electrode distance of 1.5 cm, reducing the concentration from an initial 5526 mg/L to 1225 mg/L (77.83%). Under the same condition, hardness decreased from 580 mg/L to 164 mg/L (71.72%). Regarding voltage variation, the greatest reduction in TDS and hardness was observed at 25 V, reaching 1090 mg/L (80.28%) and 176 mg/L (69.66%), respectively. The optimal treatment time was 60 minutes, resulting in a TDS reduction to 1100 mg/L (80.09%) and a hardness reduction to 186 mg/L (67.93%). Inter-electrode distance, applied voltage, and contact time were found to have a significant effect on the electrocoagulation process in reducing TDS and hardness levels, as confirmed by ANOVA analysis.